2013
DOI: 10.4103/0019-5154.110862
|View full text |Cite
|
Sign up to set email alerts
|

Multiple dermatofibromas: Dermoscopic patterns

Abstract: Dermatofibromas are benign skin lesions that consist of pigmented papules or nodules. They produce the dimple sign when laterally squeezed and are usually found on the legs. These clinical features lead to the diagnosis in most cases. However, the differential diagnosis with other lesions, such as atypical nevi and melanoma can be difficult, and the dermoscopy may help the diagnosis. There are several dermoscopic patterns associated with dermatofibromas, the most common being a central white scar like patch wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
0
11
0
2
Order By: Relevance
“…DFSP lacks cytological polymorphism and epidermal changes and has a tighter fusiform pattern with CD34 positivity . There are a limited number of studies investigating histopathological and dermatoscopic features of dermatofibromas in the literature . As far as we aware, the present study is the first to evaluate both histopathological and dermatoscopic features of dermatofibromas.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…DFSP lacks cytological polymorphism and epidermal changes and has a tighter fusiform pattern with CD34 positivity . There are a limited number of studies investigating histopathological and dermatoscopic features of dermatofibromas in the literature . As far as we aware, the present study is the first to evaluate both histopathological and dermatoscopic features of dermatofibromas.…”
Section: Discussionmentioning
confidence: 90%
“…13,14 There are a limited number of studies investigating histopathological and dermatoscopic features of dermatofibromas in the literature. 1,[5][6][7]10,11,13,15 As far as we aware, the present study is the first to evaluate both histopathological and dermatoscopic features of dermatofibromas. However, we implemented a preliminary assessment of digital microscopic features of dermatofibroma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the present case demonstrated that CM could also simulate DFs on dermatoscopy. Therefore, a skin biopsy must be undertaken in all doubtful cases, particularly in high‐risk patients and/or with a history of cancer …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a skin biopsy must be undertaken in all doubtful cases, particularly in high-risk patients and/or with a history of cancer. 10…”
Section: Discussionmentioning
confidence: 99%